Students’ Factors Difficulty in Learning Mathematics at State Elementary School 42 Pekanbaru - Sarah Syahrani Lubis; Siti Quratul Ain (CV. Creative Tugu Pena, 2022)
The problem in this study is a factor in students' learning difficulties in learning mathematics at class IV of State Elementary School (SDN) 42 Pekanbaru. The article was to describe how the factors of student learning difficulties in learning mathematics and to describe the efforts of teachers to face difficulties in learning mathematics in the classroom. This study used qualitative research with descriptive qualitative research. The subjects of this study consisted of 1 teacher and 7 students of the fourth grade at SDN 42 Pekanbaru. Data collection techniques used interviews, observation and documentation. This research also used two triangulations, namely technical triangulation and source triangulation. The place of this research was conducted at class IV SDN 42 Pekanbaru, which is located at Adi Sucipto Sidomulyo Timur Street, Marpoyan Damai District, Pekanbaru City, Riau Province. The results showed that the learning difficulty factor for students was an internal factor which was a factor originating from the student itself, stating that the factors that influenced students such as; lack of interest in learning, lack of motivation to learn, lack of self-confidence, lack of concentration while studying, lack of self-awareness of students and lack of understanding of student learning. They have difficulty in learning mathematics. The efforts to overcome these learning difficulties gave an apperception at the beginning of learning, using and explaining the material in a fun way, providing enrichment and self-evaluation of individuals, making improvements and assessing the results of learning tests by giving praise and rewards to students who are able to follow the learning process well. After that, the teacher must close the lesson so that students feel more cared for, because they already feel tired of learning, such as inviting singing and playing. Keywords : Students ‘ Factor Difficulty, Factor Difficulty Learning, Learning Difficult